Protein kinase C (PKC) inhibitor Calphostin C activates PKC in a light-dependent manner at high concentrations via the production of singlet oxygen - Ishii, Tomomi; Kajimoto, Taketoshi; Kikkawa, Satoshi; Narasaki, Soshi; Noguchi, Soma; Imamura, Serika; Harada, Kana; Hide, Izumi; Tanaka, Shigeru; Tsutsumi, Yasuo M.; Sakai, Norio (European journal of pharmacology, 2024)
Calphostin C (Cal-C) is a protein kinase C (PKC) inhibitor that binds to its C1 domain. The aim of the present study was to elucidate the action of Cal-C in addition to PKC inhibition. First, we confirmed that Cal-C at low concentrations (<200 nM) inhibit phorbol ester-induced PKC translocation and G-protein-coupled receptor (GPCR)-mediated PKC activation. Cal-C at higher concentrations (>2 μM) increased intracellular calcium ion concentrations ([Ca2+]i) in a concentration-dependent manner. The origin of this increase is the mobilization of the endoplasmic reticulum (ER), which does not involve GPCR or ryanodine receptors. Cal-C at high concentrations also cause structural changes in the ER, such as the formation of vacuoles and aggregates, and calcium leakage from the ER. At 2 μM, Cal-C translocated a calcium-sensitive PKCα. Studies using a C-kinase activity reporter and a myristoylated alanine-rich protein kinase C substrate fused with green fluorescent protein (GFP) have also revealed that Cal-C at high concentrations activate PKC in living cells. Additionally, the PKC-activating effects of Cal-C were light-dependent. Finally, studies using Si-DMA, an indicator of singlet oxygen, showed that Cal-C at high concentrations generated singlet oxygen, causing structural changes in the ER and leakage of calcium into the cytosol, which triggered PKC activation. This study confirms the novel action of Cal-C, solely considered a PKC inhibitor. Cal-C acted as a PKC inhibitor at low concentrations and a PKC activator at high concentrations by generating singlet oxygen in a light-dependent manner, suggesting that Cal-C can be used in photodynamic therapy. •Cal-C, which has been considered a PKC inhibitor, exhibits PKC activating activity at high concentrations.•Cal-C at high concentrations activate PKC by inducing changes in endoplasmic reticulum morphology and an increase in intracellular calcium.•Cal-C at high cencetrations generate singlet oxygen in a light-dependent manner and are cytotoxic.•Normal cells and several cancer-derived cells showed similar effects.